Crise politique et transnationalisation de l’État en Amérique latine : une interprétation théorique - Nef, Jorge (Études internationales, 1986)
If the crisis of the state has been a common trait in Latin America, its manifestations have not been the same throughout the continent. This article examines two general and apparently contraditory trends : the trend toward authoritarian capitalism resulting from the crisis of hegemony in South America and the trend towards popularly-based insurgency resulting from a crisis of domination in most of Central America. The author bases his general interpretation of these trends on the analysis of the historical and structural relationships between four factors identified as responsible for the drastic change in the role of the state, from "national development" to "national security" : the crisis in the model of accumulation, the growing polarization of political alliance, the transnationalization of the civil society and the state, and the interplay between relative autonomy of the state and transnationalization. He finds that the combination of transnational integration of the Latin American elites into one U.S.-centered project with hegemonic pretensions, and a growing marginalization and alienation on the part of the bulk of the internal constituencies has brought about an acute crisis of both legitimation and domination. As violence becomes the most common political currency -with repression and plain state terrorism evolving into a distinct style of politics - and the prospects towards redemocratization being very fragile, the author concludes that revolutionary struggles may be the only possibility for an indigenous redefinition of development, national self-determination and democracy.